Epidemiological features of dengue fever in a four-year hospitalbased study in Faisalabad, Pakistan - Raza, Faiz Ahmed; Iqbal, Mazhar; Ahmad, Jameel; Hussain, Shahida (Journal of Fatima Jinnah Medical University, 2018)
Background: Pakistan, being a subtropical country, is a source of various vector-borne diseases including dengue, malaria, chikungunya, Congo fever etc. Dengue fever has recently become a rapidly emerging infection with abundant morbidity and mortality in this region. Objectives: Current study undertakes to determine the epidemiological features of dengue patients reported to a tertiary care hospital in Faisalabad, Pakistan. Patients and methods: This four-year (2014-2017) retrospective cross-sectional study was carried out at Allied Hospital Faisalabad. Data of the hospitalized dengue patients was studied for demographic details, travel history to the dengue endemic areas, diagnostic information and impact of co-morbidities on the severity of the disease. Furthermore, usefulness of Google Earth® software was explored for tracking of dengue cases. Results: A total of 155 confirmed dengue cases were reported including 27% females and 73% males with a mean age of 29.5 years. Among them, 93.5% were reported with dengue fever, while 6.5% were reported with dengue hemorrhagic fever. Three different dengue serotypes were detected in the patients including DENV-1 (7.7%), DENV-2 (17.9%) and DENV-3 (74.4%). Malarial co-infection was detected in 13% of the dengue cases among which 10.5% developed severe dengue fever. Map of the city built in Google Earth® showed that 76% patients were reported from highly populated Central region of the city. Total 28 cases reported with dengue infection having travel history to Lahore, Rawalpindi, Karachi and Islamabad. Additionally, 04 international travelers with dengue infection coming from Saudi Arabia, Malaysia and Rwanda were also reported to Faisalabad. Conclusions: Circulation of various dengue serotypes in Faisalabad population require urgent attention of the public health authorities and policy makers to deal with the escalating problem of dengue fever in Pakistan.